A new concept of waste iron recycling for the enhancement of the anammox process. (November 2022) - Liu, Wenru; Li, Tianhao; Wang, Jianfang; Shen, Yaoliang; Ji, Xiaoming; Yang, Dianhai
Abstract: As a by-product of industry, waste iron scraps (WIS) are low-cost and widely available, which was potential for the development of iron-assisted anammox. In this study, the feasibility of adding WIS to enhance the nitrogen removal of the anammox process (also called WIS-assisted anammox) was demonstrated. Results indicated that the WIS-assisted anammox reactors performed a 15–35% higher nitrogen removal efficiency than that of the control. Compared to the sludge from the control, the sludge from the WIS-assisted anammox reactors had a higher iron content (78–113 g kg −1 SS) and a better specific anammox activity (10.8–15.5 mg N g −1 VSS h −1 ). The enhanced growth of the anammox bacteria (related to Ca. Kuenenia stuttgartiensis with 99% similarity) in the WIS-assisted anammox reactors was also confirmed by high-throughput sequencing and qPCR. Furthermore, the functional genes predicted by PICRUSt2 revealed a higher level of hydroxylamine oxidoreductase ( hao )-like proteins expression of the biomass from the WIS-assisted anammox reactors, implying that the hydroxylamine-related anammox pathway was promoted. Additionally, the observation of cytoplasmic nitrate reductase (narG), copper-containing nitrite reductase (nirK), and nitric oxide reductase (norB) suggested that the introduction of WIS might promote the denitrification ability. This was correlated to the lower ΔNO3 - /ΔNH4 + ratio observed in these WIS-assisted anammox reactors. Overall, the WIS-assisted anammox offers a sustainable nitrogen removal process for wastewater treatment with waste iron recycling. Graphical abstract: Image 1 Highlights: The feasibility of the WIS-assisted anammox process was demonstrated. WIS enhanced the nitrogen removal of the anammox process by 15–35%. WIS promoted the activity and growth of the anammox bacteria.